2020
DOI: 10.4314/jas.v34i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Proximate compositions and length-weight relationships of hybrid catfish, <i>Clarias gariepinus (♂) X Heterobranchus bidorsalis</i> (♀) under various densities

Abstract: The study evaluated proximate compositions, length-weight relationships, condition factor and the survival rates of hybrid catfish, Clarobranchus (Clarias gariepinus (male) X Heterobranchus bidorsalis (female) reared at different densities in tarpaulin tanks. Fish were stocked at densities of 25, 50, 75 and 100fish/m3. Each treatment was replicated three times. Fish were fed with commercial catfish feed (45% crude protein) at 5% body weight for 84 days. Length and weight data collected were analyzed with FISAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, proximate composition of fish differs from species to species, individual to individual, considering size, sex, season, feeding, and processing stress [18][19][20][21]. Many studies have reported channel catfish baseline proximate composition [22][23][24], while data for hybrid catfish proximate composition in the process lines are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, proximate composition of fish differs from species to species, individual to individual, considering size, sex, season, feeding, and processing stress [18][19][20][21]. Many studies have reported channel catfish baseline proximate composition [22][23][24], while data for hybrid catfish proximate composition in the process lines are scarce.…”
Section: Introductionmentioning
confidence: 99%